Topology optimization for multi-layer multi-material composite structures. Issue 5 (4th May 2023) - Alfouneh, Mahmoud; Hoang, Van-Nam; Luo, Zhen; Luo, Quantian
Abstract : This article investigates topology optimization of multi-layer multi-material composite structures under static loading. A moving iso-surface threshold optimization method, previously well defined for single or cellular materials, is extended to multi-layer multi-material structures using a physical response function discrepancy scheme. It is also integrated with an alternating active-phase algorithm as an alternative procedure. The proposed methods are applied to three types of objective functions, namely, minimizing compliance, maximizing mutual strain energy and minimizing full-stress designs. The corresponding response functions relevant to each optimization problem according to the proposed topology optimization methods are strain energy density, mutual strain energy density and von Mises stress, respectively. Examples are presented and compared with those available in the literature to verify the derived formulations on topology optimization for multi-layer multi-material structures. Highlights Optimization by integrating MIST with alternating active phase for multi-materials Extended MIST to topology optimization for multi-layer and multi-materials Multimaterial design to maximize mutual energy, minimize compliance and full stress